ISOLATION AND IDENTIFICATION OF ANTIOXIDANT CONSTITUENTS FROM EXTRACELLULAR METABOLITES OF LACTOBACILLUS BREVIS - Noureen; A. Riaz; E. Ali; I. Sajid; W. Zaman; N. Arshad (Journal of Animal and Plant Sciences, 2022)
Oxidative stress is a metabolic condition characterized by excessive production of free radicals in the body. The condition leads to metabolic diseases including; aging, diabetes, atherosclerosis, myocardial infarction and cancer. Antioxidants are the mainstay to modulate the consequences of oxidative damage. Secondary metabolites from lactic acid producing bacteria possess antioxidant activity. The present study aimed at isolating and identifying antioxidant metabolites present in cell free supernatant (CFS) of broth culture of Lactobacillus brevis MG 000874. Thin layer chromatography (TLC) coupled bioautography of different fractions of methanol extract of CFS using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) model indicated antioxidant activity in ethyl acetate fraction. Fourier transform infrared (FTIR) spectroscopy of the isolated compound revealed the presence of aldehyde and alkyl functional groups. GC-MS analysis led to identification of four active compounds viz. a) L-proline, N-valeryl, hexyl ester b) Ergotaman-3',6',18-Trione,12'-Hydroxy-2'-Methyl-5'-(2-Methylpropyl) c) 2-Methylthiolane, S, S-Dioxide and d) Phenol, 3,5-Bis(1,1-Dimethylethyl). Findings of present study may be useful in developing antioxidant drugs from bacterial origin.
Keywords: Lactobacillus brevis MG 000874; antioxidant; cell free supernatant; TLC coupled bioautography; GCMS; FTIR